Panton-Valentine Leukocidin-Producing Staphylococcus aureus Infection: A Case Series - Prista-Leão, B (2020)
Panton-Valentine leukocidin-producing Staphylococcus aureus (PVL-SA) is associated with relapsing multifocal skin and soft tissue infections (SSTI), necrotizing pneumonia (NP) and severe musculoskeletal infections. Epidemiology is underknown and underdiagnosis is likely. Recent travel abroad, case clustering and relapsing disease are often reported. We reviewed all cases of PVL-SA infection diagnosed at our center, and found 21 cases over a 43-month period. Most patients were adult males, had relevant travel history, reported recurrent disease and presented with SSTI. Etiologic diagnosis took up to five years; meanwhile, 42% of patients had antibiotic treatments. Draining procedures were required in 43% of patients and intensive care support in 19%. All patients recovered. Methicillin-resistance prevalence was 24%. Only 2/13 decolonized patients had posterior relapsing SSTI, both with likely infected contacts. PVL-SA infection's severity and impact are clear, even in small case series as ours. Physician awareness and active PVL-gene search are crucial for an adequate management.